Framework to analyze the use of colors in informational maps related to Covid-19 data - Klohn, Sara; Zimmermann, Anelise (InfoDesign, 2021)
This paper presents a study about using colors in maps that present information related to the Covid-19 pandemic. A sample was collected from two different governmental websites of the state of Rio Grande do Sul, Brazil. An analysis framework was developed based on the sample and drew from a literature review about the use of colors and maps in data visualization. The analysis showed that one of the examples collected presents an inconsistent use of colors, which could prompt difficulties in visualizing the data; the other example uses color more consistently, potentially being more effective in communicating information. In addition, the study showed potential for continuity and expansion due to the relevance of information design applied to health information.